EXPLORING THE USE OF DIGITAL WRITING TOOLS TO ENHANCE CREATIVE WRITING IN THE SECOND SEMESTER OF THE ENGLISH DEPARTMENT, QAMARUL HUDA BADARUDDIN UNIVERSITY 2024 - Wahab, Abdul; Ahmad Syukron Sidik; Fitria Ningsih; Rafida Rahim (PENA : Jurnal Pendidikan Bahasa, Sastra, & Pengajaran, 2024)
This study explores the effectiveness of digital writing tools in enhancing creative writing skills among second-semester students in the English Department at Qamarul Huda Badaruddin University in 2024. With the increasing integration of technology in education, digital tools offer innovative ways to support and improve students' writing abilities. This research aims to assess the current creative writing skills of students, identify the digital writing tools they frequently use, evaluate the impact of these tools on their writing, and understand their perceptions towards the use of technology in the writing process. A mixed-method approach was employed, combining quantitative surveys, qualitative interviews, and analysis of writing samples. Participants included second-semester students who underwent a pre-test to evaluate their initial creative writing skills. Following this, they received training and used various digital writing tools throughout the semester. A post-test assessed any improvements in their writing abilities, complemented by follow-up interviews to gather in-depth insights into their experiences. The results indicated a significant improvement in students' creative writing skills, as evidenced by higher post-test scores. Students reported increased motivation, better organization, and enhanced creativity when using digital tools. Commonly used tools included word processors, grammar checkers, and creative writing software, which collectively contributed to a more engaging and effective writing process. This study concludes that digital writing tools can substantially enhance creative writing skills among university students. The findings provide practical recommendations for educators to incorporate these tools into their teaching methods, thereby fostering a more interactive and productive learning environment.